Trust in government and its associations with health behaviour and prosocial behaviour during the COVID-19 pandemic - Han, Qin; Zheng, Bang; Cristae, Mioara; Agostini, Maximilian; Belanger, Jocelyn J; Gutzkow, Ben; Kreienkamp, Jannis; Reitsema, Anne Margit; van Breen, Jolien A; Abakoumkin, Georgios; Abdul Khaiyom, Jamilah Hanum; Ahmedi, Vjollca; et al. (The Society for the Improvement of Psychological Science, 2020)
Previous studies suggested that public trust in government is vital for implementations of social policies that rely on public's behavioural responses. This study examined associations of trust in government regarding COVID-19 control with recommended health behaviours and prosocial behaviours. Data from an international survey with representative samples (N=23,733) of 23 countries were analysed. Specification curve analysis showed that higher trust in government was significantly associated with higher adoption of health and prosocial behaviours in all reasonable specifications of multilevel linear models (median standardised β=0.173 and 0.244, P<0.001). We further used structural equation modelling to explore potential determinants of trust in government regarding pandemic control. Governments perceived as well organised, disseminating clear messages and knowledge on COVID-19, and perceived fairness were positively associated with trust in government (standardised β=0.358, 0.230, 0.055, and 0.250, P<0.01). These results highlighted the importance of trust in government in the control of COVID-19.